Станислав Пташицкий в России и в Польше - Kijas, Artur (My University, 2013)
Stanisław Ptaszycki (1853–1933) graduated from the Faculty of History and Philology of Saint Petersburg University. He was a philologist and historian as well as expert on Russian literature and culture, who spent almost forty years of his life on the Neva River. As early as in the 1870s he started looking for Polish historical documents in the archives and libraries of St. Petersburg. The documents he found were systematically published both in Russian and Polish. In May 1890, in recognition of his achievements related to the printed works, he obtained the right to give lectures at Saint Petersburg University as an assistant professor. From the end of the 19th century until 1918 he simultaneously taught Russian language and literature at Saint Petersburg Roman Catholic Theological Academy, first as a lecturer and then as a professor. He was also engaged in activities for Polish emigrants in St. Petersburg. After leaving Petrograd, i.e. in 1918, he came to Poland where he started working at the Catholic University of Lublin and later at Stefan Batory University in Vilnius as a professor. In 1922 he became a member of a special commission for the recovery of Polish art that had been illegally exported to Russia. In 1926 he took up a position of director-general of the State Archives. He left extensive writings in many branches of the humanities. He was called an ambassador for learning and culture in the capital of Russia both by Poles and Russians. He presented the achievements of Russian history and literature in Polish writings.
Stanisław Ptaszycki in Russia and in Poland
Stanisław Ptaszycki w Rosji i w Polsce